CpG content in the Zika virus genome affects infection phenotypes in the adult brain and fetal lymph nodes - Udenze, Daniel; Trus, Ivan; Berube, Nathalie; Karniychuk, Uladzimir (Frontiers in Immunology, 2022)
Increasing the number of CpG dinucleotides in RNA viral genomes, while preserving the original amino acid composition, leads to impaired infection which does not cause disease. Beneficially, impaired infection evokes antiviral host immune responses providing a cutting-edge vaccine approach. For example, we previously showed that CpG-enriched Zika virus variants cause attenuated infection phenotypes and protect against lethal challenge in mice. While CpG recoding is an emerging and promising vaccine approach, little is known about infection phenotypes caused by recoded viruses in vivo, particularly in non-rodent species. Here, we used well-established mouse and porcine models to study infection phenotypes of the CpG-enriched neurotropic and congenital virus—Zika virus, directly in the target tissues—the brain and placenta. Specifically, we used the uttermost challenge and directly injected mice intracerebrally to compare infection phenotypes caused by wild-type and two CpG-recoded Zika variants and model the scenario where vaccine strains breach the blood-brain barrier. Also, we directly injected porcine fetuses to compare in utero infection phenotypes and model the scenario where recoded vaccine strains breach the placental barrier. While overall infection kinetics were comparable between wild-type and recoded virus variants, we found convergent phenotypical differences characterized by reduced pathology in the mouse brain and reduced replication of CpG-enriched variants in fetal lymph nodes. Next, using next-generation sequencing for the whole virus genome, we compared the stability of de novo introduced CpG dinucleotides during prolonged virus infection in the brain and placenta. Most de novo introduced CpG dinucleotides were preserved in sequences of recoded Zika viruses showing the stability of vaccine variants. Altogether, our study emphasized further directions to fine-tune the CpG recoding vaccine approach for better safety and can inform future immunization strategies.